Instance of Lean Management implementation in the automotive industry - Kozioł, Monika; Muc, Adam; Szeleziński, Adam (Zeszyty Naukowe Gdańskiej Szkoły Wyższej, 2019)
The article presents a comparative analysis of companies incorporated into the Toyota group. The automotive market’s sales in the Middle-East Europe were discussed. 14 Toyota’s principles were described on which Toyota’s techniques, tools of production system and general company management are based. Comparison between Toyota’s factories and standard factories was made.